New Marketing Strategy: Mobile Applications as Marketing Tools in Airports - Florido-BenÃtez, Lazaro (Indian Journal of Computer Science, 2016)
Mobile applications (apps) on smartphones are being increasingly used to access news, entertainment, weather forecast, etc. As apps gain a stronger footing in the 21st century, large airports are taking advantage of this new marketing outlet by developing apps for branding and business communication. In recent years, this marketing model has established itself as a communication tool because of its multi- functionality, which provides added-value to the service content offered. This aims of the research were twofold. First, to evaluate how an airport app is having a direct and positive influence on passengers' sense of security. Second, to analyze how this tool can improve passengers' satisfaction and their perceived image of an airport. To analyze the influence an app has on passengers-users at airports, 103 passenger-users were surveyed. The results are particularly relevant for passengers as they are more efficient during their leisure time in terminals, and their stress levels decreases. Besides, by having a mobile app, airports can improve their brand image as well as enrich the experience of passengers within the airport.